A Process Optimization Method of the Mini-LOCOS Field Plate Profile for Improving Electrical Characteristics of LDMOS Device - Shaoxin Yu; Weiheng Shao; Pei-Xiong Gao; Xiang Li; Rongsheng Chen; Bin Zhao (IET Circuits, Devices and Systems)
In this work, the effects of the mini-local oxidation of silicon (LOCOS) field plate’s bottom physical profile on the devices’ breakdown performance are analyzed through technology computer-aided design simulations. It is indicated that the “abrupt” bottom profile could certainly do with an optimization. This paper introduces an effective process improvement method by etching bias power adjustment and time reduction. The upgradation of the field plate physical profile has been proved by transmission electron microscope cross-section analysis. The angle for the bottom surface of mini-LOCOS field plate θ2 is improved from 11.9° to 12.6°, and the thickness ratio of Hup/Hbottom (field plate oxide thickness for the upper and bottom, respectively) is increased from 71.8% to 76.6%. Finally, the optimized laterally diffused metal oxide semiconductor devices have been fabricated, and both figure of merit curves and safe operation area curves are measured. The specific on-resistance Ron,sp could achieve as low as 11.3 mΩ mm2, while breakdown voltage BVds,max arrives at 37.4 V, which is nearly 19.3% improved.